Advancing muscle aging and sarcopenia research through spatial transcriptomics - Byeong-Don Min; Chae Young Hwang; Doyeong Kim; Sang-Yun Kim; Jayasinghage Nirmani Chathurangika Jayasinghe; Minh Nhat Tran; Sang-Min Park; Ki-Sun Kwon (Osteoporosis and Sarcopenia, 2025)
Sarcopenia, defined as a decline of muscle mass and function with aging, poses significant health challenges. This decline is driven by multiple factors including cellular dysfunction, mitochondrial impairments, oxidative stress, and chronic inflammation, all of which collectively disrupt muscle homeostasis and regeneration. Despite the lack of approved treatments for sarcopenia, the search for effective therapies continues as various pharmacological interventions are currently in the early stage of development. Recent advances in transcriptomics have enhanced our understanding of the molecular and cellular mechanisms underlying skeletal muscle aging. In particular, spatial transcriptomics (ST) has revolutionized the field of sarcopenia research by capturing the spatial context of gene expression to uncover site-specific regulation and cellular interactions within tissues. In this review, we explore the current knowledge of sarcopenia, the mechanisms underlying muscle aging, and recent developments in therapeutic strategies. Furthermore, we examine recent studies employing ST that have provided critical insights into the spatial heterogeneity of muscle aging and atrophy, revealing novel cellular and molecular targets for intervention. By connecting muscle pathophysiology with spatial information, ST holds promise for guiding the development of novel sarcopenia therapies, ultimately improving outcomes for aging populations worldwide.